Avaliação de um protocolo MAC sem fio full duplex - Garcia, Georgia (2016)
The advance of self-interference cancellation techniques allowed the development of Full Duplex (FD) radios, i.e. radios capable of doubling the capacity of a Half Duplex link by sending and receiving data at the same time. An important question raised by such advance consists in determining if a MediumAcess Protocol (MAC) can scale FD gains in a network with an increasing amount of nodes. In this context, this study will evaluate the FD MAC protocol PbP-EDCA (Piece-by-Piece - Enhanced Distributed Channel Access) in noisy channels. The PbP-EDCA protocol is an FD extension of the IEEE 802.11 MAC for wireless local area networks. The protocol was first implemented in Java, and then can be evaluated in a FD wireless network scenario in comparison to IEEE 802.11’s CSMA/CA. Different scenarios were evaluated using the protocol PbP-EDCA with 2 subchannels of 10 MHz, PbP-EDCA using 4 subchannels of 5 MHz, and IEEE 802.11 DCF CSMA/CA with one channel of 20 MHz. It was observed that PbP-EDCA with 4 subchannels has the best performance except in cases of intense noise, here, -82 dBm.